DISTRIBUTION OF HEALTH FACILITY SERVING CATARACT SURGERY IN SOUTH SULAWESI - ARIFFIN, ANNISA IKHSANIAH; Amalius, Ahmad ashraf; Faisal, Andi Akhmad; Kamaruddin, Muhammad Irfan (Ophthalmologica Indonesiana, 2024)
Introduction & Objectives One of the elements in Vision 2020: the right to sight is the fulfillment of resources to reduce avoidable blindness. According to the Indonesian’s prevention of blindness roadmap about sources, we need to collect the data about health facilities serving cataract surgery. The aim of this study is to provide the data about health facilities serving cataract surgery in South Sulawesi Province. Methods A descriptive study using a questionnaire which is distributed to hospitals/clinics in South Sulawesi Province. In addition, secondary data was also used from previous research conducted by one of the residents of Ophthalmology at Hasanuddin University. All the data were collected from Januari to June 2022. Results The distribution of health facilities in all districts/cities in South Sulawesi has at least one health facility serving cataract surgery, with the most distribution in Makassar. Twelve of 62 hospitals and five of 27 eye clinics have not provided cataract surgery services..There are 6 districts (25%) that have not fullfil the minimum number standard of ophthalmologist according to WHO. All district/cities in the Province have all the instrument required for cataract surgery. Conclusion Every district/city in South Sulawesi has at least one health facility serving cataract surgery. Information on the distribution of health facilities serving cataract surgery needs to be routinely conducted twice a year according to Indonesian’s prevention of blindness roadmap.